Penerapan Metode Waterfall Dalam Perancangan Sistem Informasi Keuangan Di Pondok Pesantren Cipasung - Mohammad Sabar Jamil; Riezan Syauqi Fanhas; Vira S. Alpiah; Moh. Milki I. M (Cipasung Techno Pesantren: Jurnal Ilmiah, 2022)
Cipasung Islamic Boarding School is an Islamic religious education institution located in Singaparna, Tasikmalaya. Cipasung Islamic Boarding School was founded in 1931 AD by the late almaghfurlah KH. Ruhiat. Cipasung Islamic Boarding School is an institution whose financial management is still done manually. This can cause data to be lost or damaged, besides that it can cause confusion between the hostel and the parents of the students. The confusion that occurred between the boarding house and the parents of the students was caused by the parents not having access to find out their child's monthly tuition payment report. It is necessary to design a financial information system that is appropriate for the problems that occur at the Cipasung Islamic Boarding School. In this study, the Waterfall model SDLC method will be used. With object-oriented modeling using the Unified Modeling Language (UML), data-oriented modeling using DFD, and database modeling using ERD. The design of the financial information system that has been done can be a better way to minimize the problems that occur.